Resistor and Capacitor Time Constant Measuring Instrument Using Arduino UNO - Prayogi, Soni; Silviana, Fitria; Saminan, Saminan (Jurnal Ilmiah Pendidikan Fisika Al-Biruni, 2023)
The most interesting problem to be discussed in electrical physics is one-way electric circuits. In this work, the researchers constructed an experimental setup for determining the time constant of DC resistors and capacitors using the open-source Arduino UNO hardware platform. Arduino UNO was a signal generator for data collection systems and a simple signal visualization instrument. Experiments were carried out using an analog oscilloscope combined with theoretical calculations. The results show that, on a spreadsheet, the data processing and fitting of the curves for the six Resistor and Capacitor test sets yielded values determined by the component tolerances. The researchers believe that the design of this equipment and software demonstrates the recommended suitability, making it flexible for use in teaching and learning in laboratory contexts.